Abrasive Slurry

The abrasive slurry, composed of cerium oxide and magnesium hydroxide abrasive grains, addresses the issue of decreasing polishing rates in CMP methods by maintaining a stable performance over time, thus enhancing the efficiency and reducing costs.

JP7659703B2Active Publication Date: 2025-04-09MITSUI MINING & SMELTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024529688
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-02
Filing Date
2024-02-01
Publication Date
2025-04-09
Estimated Expiration
2044-02-01

AI Technical Summary

Technical Problem

The existing abrasive compositions used in CMP methods, particularly those containing fine cerium oxide particles, lead to a decrease in polishing rate over time and increased management costs due to the need to maintain the polishing rate.

Method used

An abrasive slurry comprising cerium oxide abrasive grains, magnesium hydroxide abrasive grains, a dispersant, and a solvent, with an average abrasive grain diameter of 0.01 μm to 0.5 μm, which suppresses the reduction in polishing rate due to changes over time.

Benefits of technology

The proposed abrasive slurry effectively maintains a stable polishing rate over time, even with fine abrasive grains, thereby reducing management costs and improving the overall efficiency of the CMP process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659703000001
    Figure 0007659703000001
Patent Text Reader

Abstract

This abrasive slurry contains cerium oxide abrasive grains, magnesium hydroxide abrasive grains, a dispersant, and a solvent, and the cerium oxide abrasive grains and the magnesium hydroxide abrasive grains have an average particle size of 0.01 to 0.5 μm inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an abrasive slurry. [Background technology]

[0002] As semiconductor elements become increasingly dense and precise, the CMP (Chemical Mechanical Polishing) method was developed as a technology for flattening the surface of a thin film formed by a method such as CVD (Chemical Vapor Deposition) in the semiconductor wafer manufacturing process.

[0003] The performance of the CMP method is greatly influenced by the selection of the abrasive slurry and the polishing pad. In particular, the selection of the abrasive slurry is a factor that greatly affects the performance of the CMP method. The abrasive slurry used in the CMP method includes silicon dioxide (SiO 2 ) and cerium(IV) oxide (CeO 2 ) is included as abrasive particles. For example, Patent Document 1 discloses an abrasive composition containing cerium oxide fine particles as abrasive grains. Here, the abrasive composition disclosed in Patent Document 1 contains cerium oxide fine particles having a purity of 99 mass% or more (the average particle size (D50) is 0.01 μm to 1.0 μm), a chelating agent, a dispersant having a polyacrylic acid group or a polymethacrylic acid group, and elements such as Mg, Al, K, and C (the content of which is 30 ppm or less). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2001 / 080296 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the polishing composition disclosed in Patent Document 1 has a drawback in that the polishing rate decreases with time because the cerium oxide particles contained as abrasive grains are fine, and the management cost of the polishing material increases in order to maintain the polishing rate in the polishing process.

[0006] In view of the above problems, the present invention provides an abrasive slurry that can suppress a decrease in polishing rate due to changes over time even when the grain size of the abrasive grains is fine. [Means for solving the problem]

[0007] The abrasive slurry of the present invention, which has been made to solve the above problems, comprises cerium oxide-based abrasive grains, magnesium hydroxide-based abrasive grains, a dispersant, and a solvent, and is characterized in that the average grain size of the cerium oxide-based abrasive grains and the magnesium hydroxide-based abrasive grains is 0.01 μm or more and 0.5 μm or less. The abrasive slurry of the present invention contains cerium oxide-based abrasive grains, magnesium hydroxide-based abrasive grains, a dispersant, and a solvent, and therefore can suppress a decrease in the polishing rate due to changes over time even if the average abrasive grain size of the cerium oxide-based abrasive grains and the magnesium hydroxide-based abrasive grains is as fine as 0.01 μm or more and 0.5 μm or less.

[0008] As the cerium oxide-based abrasive grains, cerium oxide abrasive grains are preferred, specifically cerium oxide (IV) and cerium oxide (III), and cerium oxide (IV) is preferred from the viewpoint of material stability. The cerium oxide-based abrasive grains may be a mixture of one or more types of cerium oxide-based particles. The cerium oxide-based abrasive grains may contain other elements such as F (fluorine), Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. In particular, the cerium oxide-based abrasive grains may contain other elements such as F (fluorine), La, Pr, and Nd.

[0009] The abrasive slurry of the present invention contains magnesium hydroxide abrasive grains in addition to the above-mentioned cerium oxide abrasive grains. The magnesium hydroxide abrasive grains adsorb the polishing dust (fine powder after polishing) of the object to be polished to the cerium oxide abrasive grains, and suppress the deterioration of the polishing performance, so it is presumed that they function as an additive. For example, magnesium hydroxide abrasive grains are preferable as the magnesium hydroxide abrasive grains. In addition, the magnesium hydroxide abrasive grains may be a mixture of one or more types of magnesium hydroxide particles. In addition, the magnesium hydroxide abrasive grains may contain other elements such as Ca, Si, Fe, Al, S, and B. In particular, they may contain other elements such as Ca and Si.

[0010] The abrasive slurry of the present invention contains the cerium oxide-based abrasive grains and magnesium hydroxide-based abrasive grains described above, as well as a solvent and a dispersant described below. Since the cerium oxide-based abrasive grains are easily agglomerated when they are fine, the presence of a dispersant improves the dispersibility in the solvent.

[0011] In the abrasive slurry of the present invention, the average particle size of the cerium oxide abrasive grains and magnesium hydroxide abrasive grains is preferably 0.01 μm or more and 0.5 μm or less, from the viewpoint of suppressing a decrease in the polishing rate and reducing the surface roughness Ra of the polished surface. The average particle size of the cerium oxide abrasive grains and magnesium hydroxide abrasive grains is more preferably 0.05 μm or more and 0.2 μm or less.

[0012] Here, the average particle size of the cerium oxide-based abrasive grains and magnesium hydroxide-based abrasive grains is the particle size (D50) measured by particle size distribution measurement using dynamic light scattering, and can be measured as follows.

[0013] The dynamic light scattering method is a method in which a solution such as a suspension solution is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle size analysis - dynamic light scattering method". The measurement sample is a sample diluted with pure water so that the solid content concentration in the abrasive slurry of the present invention is 0.005% by mass to 0.1% by mass. The solid content concentration can be calculated as follows. First, 5 g of the abrasive slurry of the present invention is collected and heated at 180°C for 60 minutes in an air atmosphere, and the mass (Xg) of the obtained solid content is measured. Then, the solid content concentration can be calculated by calculating Xg (solid content mass) ÷ 5 g (mass of the collected abrasive slurry of the present invention) × 100. Just before the measurement, the measurement sample is filtered through a filter with a particle capture performance of 11 μm or more, and ultrasonically treated for 3 minutes with an ultrasonic cleaner (VS-100III manufactured by AS ONE Corporation). Furthermore, the liquid temperature of the measurement sample is adjusted to 25°C. The particle size (D50) refers to the median size (D50) which is the particle size showing the 50% integrated value of the integrated distribution curve.

[0014] Furthermore, from the viewpoint of achieving the object of the present application, the average grain size of the cerium oxide-based abrasive grains is preferably 0.01 μm or more and 0.5 μm or less, and may be 0.05 μm or more and 0.2 μm or less.

[0015] Moreover, from the viewpoint of achieving the object of the present application, the average grain size of the magnesium hydroxide-based abrasive grains is preferably 0.01 μm or more and 0.5 μm or less, and may be 0.05 μm or more and 0.2 μm or less.

[0016] Furthermore, in the manufacturing method of the abrasive slurry of the present invention described later, a paint shaker or a bead mill is used in the step of grinding the cerium oxide abrasive grains and the magnesium hydroxide abrasive grains. Therefore, the abrasive slurry of the present invention is produced by using ZrO 2 Or Al2 O 3 In addition, ZrO in the abrasive slurry of the present invention is 2 Or Al 2 O 3 The content of does not affect the polishing performance of the abrasive slurry of the present invention.

[0017] The abrasive slurry of the present invention is characterized in that it contains a solvent, and the solvent contains water. The abrasive slurry of the present invention has high dispersibility in water, so pure water can be used as the solvent. In addition to pure water, water-soluble organic solvents such as alcohols and ketones, or mixtures thereof are preferable in terms of sufficiently increasing the polishing rate, and water is more preferable. The content of the solvent is preferably 60% by mass or more and 99.9% by mass or less, and more preferably 80% by mass or more and 90% by mass or less, when the abrasive slurry of the present invention is taken as 100% by mass. Typically, the content of the solvent may be 98% by mass or less, 97% by mass or less, or 95% by mass or less, when the abrasive slurry of the present invention is taken as 100% by mass.

[0018] The abrasive slurry of the present invention is characterized in that it contains a dispersant, and the dispersant contains at least one selected from the group consisting of organic acid alkali metal salts, phosphoric acids, and polymer dispersants. The abrasive slurry of the present invention contains a dispersant, and the dispersant contains one or more selected from the group consisting of alkali metal salts of organic acids, phosphoric acids, and polymeric dispersants, which can suppress aggregation of the cerium oxide-based abrasive grains.

[0019] The organic acid alkali metal salt preferably includes at least one selected from sodium citrate, sodium gluconate, and sodium tartrate. The sodium citrate may include monosodium citrate, disodium citrate, and trisodium citrate. The sodium tartrate may include monosodium tartrate and disodium tartrate. The sodium tartrate may be L-, D-, or meso-form, or a mixture thereof. The organic acid alkali metal salt may be a hydrate.

[0020] Furthermore, the organic acid alkali metal salt contained in the abrasive slurry of the present invention is preferably measured by high performance liquid chromatography.The type and weight of the organic acid alkali metal salt can be measured by a known method using high performance liquid chromatography.Also, the organic acid alkali metal salt contained in the abrasive slurry of the present invention can be separated and measured.

[0021] Examples of the phosphoric acid include phosphoric acid, condensed phosphoric acid, and alkali metal salts thereof. Here, the alkali metal salts include one or more phosphoric acids selected from sodium phosphate, sodium hexametaphosphate, sodium pyrophosphate, sodium tetrapolyphosphate, and sodium ultrapolyphosphate.

[0022] Furthermore, the measurement of the phosphoric acid contained in the polishing slurry of the present invention is preferably performed by high performance liquid chromatography. In the high performance liquid chromatography, by using a non-suppressor anion analysis column, the type and weight of phosphoric acid can be measured by a known method. For example, as a non-suppressor anion analysis column, Shodex non-suppressor anion analysis column IC I-524A (manufactured by Shoko Science Co., Ltd.) can be mentioned, and by using this non-suppressor anion analysis column, the phosphoric acid contained in the polishing slurry of the present invention can be separated and measured.

[0023] Examples of the polymer dispersant include one or more water-soluble organic polymers selected from polyacrylic acid, polycarboxylic acid, polycarboxylate, and copolymers thereof. The polymer dispersant is particularly preferably a polyacrylate, and more preferably an ammonium polyacrylate.

[0024] The abrasive slurry of the present invention is characterized in that, when the abrasive slurry is taken as 100% by mass, the content of the cerium oxide-based abrasive grains is 0.5% by mass or more and 40% by mass or less, and the content of the magnesium hydroxide-based abrasive grains is 0.005% by mass or more and 20% by mass or less.

[0025] The content of the cerium oxide-based abrasive grains in the abrasive slurry of the present invention is preferably 0.5% by mass or more and 40% by mass or less, from the viewpoint of realizing a good polishing rate. The content of the cerium oxide-based abrasive grains is more preferably 3.0% by mass or more and 35.0% by mass or less, more preferably 4.0% by mass or more and 30.0% by mass or less, particularly preferably 5.0% by mass or more and 25.0% by mass or less, and most preferably 15.0% by mass or more and 25.0% by mass or less. Typically, the content of the cerium oxide-based abrasive grains in the abrasive slurry of the present invention may be 40% by mass or less, 38% by mass or less, or 36% by mass or less. The content of the cerium oxide-based abrasive grains in the abrasive slurry of the present invention is the total content of the total rare earth oxide (TREO), rare earth oxide, and F (fluorine) in the abrasive slurry of the present invention.

[0026] In addition, the content of magnesium hydroxide-based abrasive grains in the polishing slurry of the present invention is preferably 0.005% by mass or more and 20% by mass or less, from the viewpoint of suppressing the decrease in polishing rate. In addition, the content of magnesium hydroxide-based abrasive grains is more preferably 0.05% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 5% by mass or less, and particularly preferably 0.5% by mass or more and 3% by mass or less. Typically, the content of magnesium hydroxide-based abrasive grains in the polishing slurry of the present invention may be 20% by mass or less, 18% by mass or less, or 16% by mass or less. The content of magnesium hydroxide-based abrasive grains in the polishing slurry of the present invention is defined as the Mg content in the polishing slurry of the present invention.

[0027] Here, the total rare earth oxide (TREO) and rare earth oxide content is measured using an ICP-OES (inductively coupled plasma optical emission spectroscopy) or ICP-MS (inductively coupled plasma mass spectroscopy) device, and the F (fluorine) content is measured by the fluoride ion electrode method. Furthermore, the Mg content in the magnesium hydroxide-based abrasive grains is measured using an ICP-OES or ICP-MS device.

[0028] Specifically, 100 ml of the abrasive slurry of the present invention is placed in a glass beaker and dried by heating at 120°C for 24 hours to obtain a dried abrasive of the present invention. The content of each component is measured using the dried abrasive of the present invention. The total rare earth oxide (TREO) content is measured by the oxalate precipitation-calcination-gravimetry method (unit: solid: mass%, liquid: g / L). As a pretreatment, the dried abrasive of the present invention is dissolved in nitric acid, perchloric acid, and hydrogen peroxide, and boiled to obtain a measurement sample. In addition, if the measurement target is a liquid, it is not necessary to dissolve it in nitric acid or the like, and it may be boiled as it is.

[0029] In addition, the F (fluorine) content can be calculated by dissolving the solid (abrasive) to be measured in alkali fusion and hot water extraction, and measuring the F concentration in the solution using the fluoride ion electrode method, thereby calculating the F content (mass%) in the solid.

[0030] Furthermore, the Mg content can be determined as follows. Nitric acid, perchloric acid, and hydrogen peroxide are added to the dried abrasive of the present invention, which is then decomposed by heating to form a solution, and the Mg concentration can be measured using an ICP-OES device. The magnesium hydroxide content added can be estimated by multiplying this by the hydroxide coefficient. The hydroxide coefficient is Mg(OH) 2 / Mg={24.3+(16.0+1.01)×2} / 24.3≒2.40.

[0031] Furthermore, the content of the dispersant in the abrasive slurry of the present invention is preferably 0.001% by mass or more and 15% by mass or less from the viewpoint of improving dispersibility.Moreover, the content of the dispersant is more preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.005% by mass or more and 5% by mass or less, and particularly preferably 0.5% by mass or more and 3% by mass or less.Typically, the content of the dispersant in the abrasive slurry of the present invention may be 15% by mass or less, 13% by mass or less, or 11% by mass or less.

[0032] The content of the dispersant in the abrasive slurry of the present invention is measured by gel permeation chromatography (GPC), liquid chromatography (LC), or liquid chromatography-mass spectrometry (LC-MS).

[0033] In this specification, the contents of the cerium oxide-based abrasive grains, magnesium hydroxide-based abrasive grains, and dispersant in the abrasive slurry of the present invention are the contents in the polishing slurry before polishing begins, unless otherwise specified.

[0034] In the polishing slurry of the present invention, the weight ratio of the magnesium hydroxide-based abrasive grains to the cerium oxide-based abrasive grains is 1.25×10 -4 It is characterized in that it is between 40 and 40. The weight ratio of the magnesium hydroxide-based abrasive grains to the cerium oxide-based abrasive grains contained in the abrasive slurry of the present invention is 1.25×10 -4 A ratio of from 1 to 40 is preferable from the viewpoint of suppressing a decrease in the polishing rate.

[0035] Furthermore, the weight ratio of the magnesium hydroxide abrasive grains to the cerium oxide abrasive grains is more preferably 0.001 or more and 1 or less, and further preferably 0.01 or more and 0.1 or less.

[0036] Here, the weight of the cerium oxide abrasive grains in the abrasive slurry of the present invention is the total content of total rare earth oxides (TREO), rare earth oxides, and F (fluorine) as described above. The weight of the magnesium hydroxide abrasive grains in the abrasive slurry of the present invention is the Mg hydroxide content as described above. This allows the weight ratio of the magnesium hydroxide abrasive grains to the weight of the cerium oxide abrasive grains to be determined. When the cerium oxide abrasive grains contain Mg by SEM-EDX analysis of the cerium oxide abrasive grains, the weight ratio of Mg to Ce in 20 particles of cerium oxide abrasive grains is calculated as an average value from the results of semi-quantitative analysis. The weight of the magnesium hydroxide abrasive grains can be calculated by subtracting the weight of Mg contained in the cerium oxide abrasive grains from the Mg content contained in the entire abrasive slurry of the present invention.

[0037] In the polishing slurry of the present invention, the cerium oxide-based abrasive grains have a Ce content of CeO when the cerium oxide-based abrasive grains are taken as 100 mass %. 2 The La content is 100 mass% or less when converted to La. 2 O 3 The F content is 40 mass% or less in terms of F conversion, the F content is 10 mass% or less in terms of F conversion, and the Pr content is Pr 6 O 11 The Nd content is 10 mass% or less when converted to Nd 2 O 3 It is characterized in that the content is 10 mass % or less in terms of the total mass. The cerium oxide-based abrasive grains used as the abrasive grains are preferably such that the purity of the cerium oxide is higher, since the polishing rate is higher. On the other hand, when the cerium oxide particles contain impurities, it is also preferable in terms of improving the polishing rate that the ratio of rare earth elements other than cerium as the impurities is as low as possible. When the ratio of rare earth elements other than cerium, particularly lanthanum (La) and praseodymium (Pr), is low, the polishing rate is further improved.

[0038] The Ce content in the cerium oxide abrasive grains of the present invention is CeO 2It is preferable that the Ce content is 100% by mass or less in terms of realizing a good polishing rate.Moreover, it is more preferable that the Ce content is 50% by mass or more and 100% by mass or less, further more preferable that the Ce content is 60% by mass or more and 100% by mass or less, particularly preferable that the Ce content is 70% by mass or more and 100% by mass or less, more particularly preferable that the Ce content is 80% by mass or more and 100% by mass or less, and further particularly preferable that the Ce content is 90% by mass or more and 100% by mass or less.Typically, the Ce content may be 100% by mass or less, 98% by mass or less, or 96% by mass or less.

[0039] The La content in the cerium oxide abrasive grains of the present invention is 2 O 3 The La content may be 40 mass% or less in terms of La content. The La content may be 0 mass% or more and 40 mass% or less, 0.1 mass% or more and 40 mass% or less, or 20 mass% or more and 40 mass% or less. Typically, the La content may be 40 mass% or less, 38 mass% or less, or 36 mass% or less.

[0040] The F content in the cerium oxide abrasive grains of the present invention may be 10% by mass or less in terms of F. The F content may be 0% by mass or more and 10% by mass or less, or 2% by mass or more and 8% by mass or less. Typically, the F content may be 10% by mass or less, 8% by mass or less, or 6% by mass or less.

[0041] The Pr content in the cerium oxide abrasive grains of the present invention is Pr 6 O 11 The Pr content may be 10% by mass or less in terms of mass conversion. The Pr content may be 0% by mass or more and 10% by mass or less, 0.1% by mass or more and 10% by mass or less, or 2% by mass or more and 8% by mass or less. Typically, the Pr content may be 10% by mass or less, 8% by mass or less, or 6% by mass or less.

[0042] The Nd content in the cerium oxide abrasive grains of the present invention is Nd 2 O3 The Nd content may be 10% by mass or less in terms of Nd content. The Nd content may be 0% by mass or more and 10% by mass or less, 0.1% by mass or more and 10% by mass or less, or 0.1% by mass or more and 5% by mass or less. Typically, the Nd content may be 10% by mass or less, 8% by mass or less, or 6% by mass or less.

[0043] The content of each element in the cerium oxide abrasive grains of the present invention can be determined as follows. Specifically, CeO 2 / TREO can be calculated by dissolving the measurement sample obtained by the above-mentioned total rare earth oxide (TREO) measurement with perchloric acid and hydrogen peroxide, and measuring it by the ICP-OES method. 2 O 3 / TREO,Pr 6 O 11 / TREO, Nd 2 O 3 / TREO can be calculated in a similar manner.

[0044] Furthermore, the abrasive slurry of the present invention may contain any additive other than the above-mentioned cerium oxide-based abrasive grains, magnesium hydroxide-based abrasive grains, dispersant, and solvent. Here, the optional additives include dispersants, pH adjusters, viscosity adjusters, chelating agents, oxidizing agents, surfactants, and rust inhibitors. The content of the optional additives is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, when the abrasive slurry of the present invention is taken as 100% by mass. Typically, the content of the optional additives may be 10% by mass or less, 8% by mass or less, or 6% by mass or less.

[0045] A polishing method for polishing an object to be polished using the above-mentioned abrasive slurry of the present invention will be described below.

[0046] The polishing method includes supplying the abrasive slurry of the present invention to a polishing pad, contacting the polished surface of the workpiece with the polishing pad, and polishing by the relative movement between the two. Here, the method may be a method of pouring the abrasive slurry of the present invention, or a method of circulating the abrasive slurry of the present invention, in which the abrasive slurry of the present invention that has been supplied to the polishing pad and used for polishing is recovered, and the recovered abrasive slurry of the present invention is supplied to the polishing pad again by repeatedly performing the operation. Since the abrasive slurry of the present invention can be circulated and repeatedly used to polish the workpiece, the amount of use can be reduced. Here, the polishing pad can be, for example, a pad made of a nonwoven fabric that has been used conventionally, a pad made by impregnating it with a resin such as polyurethane or epoxy, or a suede material. The polishing pressure can be 5 kPa or more and 1.0 x 10 2 kPa or less, particularly 5 kPa to 5.0×10 kPa or less, is preferable in terms of polishing force and ease of handling of the polishing jig, etc. The supply rate of the abrasive slurry is preferably 10 mL / min to 2000 mL / min, and more preferably 50 mL / min to 800 mL / min.

[0047] Examples of the material to be polished by the abrasive slurry of the present invention include glass, quartz, silicon oxide, silicon (silicon wafer, etc.), and high-hardness materials with a Mohs hardness of 8 or more. Furthermore, the abrasive slurry of the present invention is expected to perform chemical mechanical polishing (CMP) by the chemical reaction of the material to be polished caused by cerium oxide. In addition, by adding an oxidizing agent, such as potassium permanganate or hydrogen peroxide, to the abrasive slurry of the present invention, a CMP process in which the chemical reaction is more effectively accelerated is also possible. The material to be polished in the CMP process is, for example, a high-hardness material with a Mohs hardness of 8 or more. Here, the Mohs hardness is a numerical value of hardness based on how a standard material is scratched, and can be measured by a conventional method using a Mohs hardness tester. Standard materials are designated on the Mohs hardness scale, with hardness levels ranging from 1 to 10, with specific standard materials being talc with a Mohs hardness of 1, gypsum with a Mohs hardness of 2, calcite with a Mohs hardness of 3, fluorite with a Mohs hardness of 4, apatite with a Mohs hardness of 5, orthoclase with a Mohs hardness of 6, quartz with a Mohs hardness of 7, topaz with a Mohs hardness of 9, corundum with a Mohs hardness of 9, and diamond with a Mohs hardness of 10. Examples of high hardness materials with a Mohs hardness of 8 or more include silicon carbide (Mohs hardness of about 9), gallium nitride (Mohs hardness of about 9), and diamond.

[0048] The object to be polished by the abrasive slurry of the present invention is preferably a silicon wafer having a silicon oxide layer on the surface, and may be a multi-layer structure or a composite material obtained by compounding a plurality of materials. In particular, for silicon, the abrasive slurry of the present invention can be used in forming an STI (shallow trench isolation) structure, flattening a premetal insulating material or an interlayer insulating material, forming a plug or embedded metal wiring, etc., in the manufacturing process of a semiconductor device having a substrate (wafer).

[0049] Next, a method for producing the above-mentioned abrasive slurry of the present invention will be described below. The method for producing the abrasive slurry of the present invention includes a production method by wet grinding and a production method by dry grinding.

[0050] Cerium oxide (abrasive grains, CeO) is used as a raw material in the manufacturing method by wet grinding or the manufacturing method by dry grinding described below. 2 ), or magnesium hydroxide (additive, abrasive grain, Mg(OH) 2 The raw material particle size of is the particle size at 50% cumulative volume fraction (D50) measured by a laser diffraction / scattering particle size distribution measurement method. Specifically, the measurement sample is prepared by diluting the raw material with water so that the concentration is about 0.01%. Then, the particle size at 50% cumulative volume fraction (D50) is measured using a laser diffraction / scattering particle size distribution measurement device (Microtrackbell Corporation: MT3300EXII).

[0051] First, the method for producing the abrasive slurry of the present invention by wet pulverization will be described below.

[0052] In a container, add pure water and cerium oxide (abrasive grains, CeO 2 ), magnesium hydroxide (additive, abrasive grain, Mg(OH) 2 ), and a dispersant (e.g., trisodium citrate), and the container is set in a paint shaker (60 Hz) and rotated at high speed to make a slurry of the mixture. Note that a bead mill may be used instead of the paint shaker.

[0053] Beads (zirconia, φ0.1 mm) are placed in the container, and the slurried mixture is wet-pulverized to pulverize the cerium oxide in the mixture.

[0054] The mixture containing the mixed and ground cerium oxide in the vessel is filtered using a filter to separate it from the beads, and the resulting slurry is collected.

[0055] The solids concentration in the collected supernatant, i.e., the concentration of cerium oxide-based abrasive grains, is measured using a heated moisture meter, and pure water is added to reach a predetermined concentration, and the abrasive slurry of the present invention is obtained by mixing.

[0056] Next, the method for producing the abrasive slurry of the present invention by dry grinding will be described below.

[0057] In the container, cerium oxide (abrasive grains, CeO 2 ) and beads (zirconia, φ0.4 mm) are placed in the container, the container is set on a paint shaker (60 Hz), and the container is rotated at high speed to dry-pulverize the cerium oxide.

[0058] The mixture containing the dry-ground cerium oxide in the container is separated from the beads using a filter, and the mixture containing the dry-ground cerium oxide is collected.

[0059] Then, the container is filled with pure water and dry-ground cerium oxide (abrasive grains, CeO 2 ), magnesium hydroxide (additive, abrasive grain, Mg(OH) 2 ), and a dispersant (eg, trisodium citrate), and the container is set on a paint shaker (60 Hz) and rotated at high speed to form a slurry of the mixture.

[0060] The collected slurry is then filtered through a filter having particle capture capability (e.g., particle capture capability of 2 μm or more), and the solids concentration in the supernatant, i.e., the cerium oxide-based abrasive grain concentration, is measured using a heated moisture meter. Pure water is then added to reach a predetermined concentration, and the mixture is mixed to obtain the abrasive slurry of the present invention.

[0061] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention

[0062] The abrasive slurry of the present invention can suppress a decrease in removal rate due to aging even if the abrasive grains have a fine grain size. [Brief description of the drawings]

[0063] [Figure 1] 1 is a table showing the physical property values ​​and measurement results of abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5. BEST MODE FOR CARRYING OUT THEINVENTION

[0064] The abrasive slurry according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.

[0065] Example 1 First, put pure water and cerium oxide (CeO 2 , raw material particle size 22.2 μm), additives and magnesium hydroxide-based abrasive grains, magnesium hydroxide (Mg(OH) 2 The mixture slurry containing cerium oxide was obtained by adding and mixing trisodium citrate as a dispersant (raw material particle size 3.5 μm). Here, when the abrasive slurry of Example 1 was taken as 100 mass%, the amount of magnesium hydroxide added was 0.78 mass%. Furthermore, when the abrasive slurry of Example 1 was taken as 100 mass%, the amount of trisodium citrate added was 0.6 mass%.

[0066] Next, the container was placed on a paint shaker (60 Hz) and rotated at high speed to dissolve cerium oxide (CeO 2 ) and magnesium hydroxide (Mg(OH) 2 ) was wet-ground so that the final average grain size of the abrasive grains would be 0.1 μm.

[0067] The mixture slurry containing the wet-milled cerium oxide in the container was filtered using a filter to separate it from the beads, and the mixture slurry was collected.

[0068] The collected mixture slurry was measured using a heated moisture meter, and pure water was added so that the solid concentration in the supernatant, i.e., the cerium oxide-based abrasive grain concentration, was 10 mass % when the abrasive slurry of Example 1 was taken as 100 mass %, thereby obtaining the abrasive slurry of Example 1.

[0069] Example 2 Example 2 is magnesium hydroxide (Mg(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the raw material particle diameter of ) was set to 6 μm, to obtain an abrasive slurry of Example 2.

[0070] Example 3 Example 3 is magnesium hydroxide (Mg(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the raw material particle diameter of ) was set to 0.15 μm, to obtain an abrasive slurry of Example 3.

[0071] Example 4 Example 4 is magnesium hydroxide (Mg(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the amount of 0.1 mass % was added, to obtain an abrasive slurry of Example 4.

[0072] Example 5 In Example 5, the same production method as in Example 1 was carried out except that the dispersant was changed from trisodium citrate to trisodium gluconate, thereby obtaining an abrasive slurry according to Example 5.

[0073] Example 6 In Example 6, the same production method as in Example 1 was carried out, except that the dispersant was changed from trisodium citrate to disodium (L)-tartrate dihydrate, to obtain an abrasive slurry according to Example 6.

[0074] Example 7 Example 7 is magnesium hydroxide (Mg(OH) 2A manufacturing method similar to that of Example 1 was carried out, except that the amount of 0.01 mass % was added, to obtain an abrasive slurry of Example 7.

[0075] Example 8 Example 8 is magnesium hydroxide (Mg(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the amount of the additive, 10 mass %, was changed to 10 mass %, to obtain an abrasive slurry according to Example 8.

[0076] Example 9 Example 9 is a cerium oxide abrasive (CeO 2 ), and magnesium hydroxide (Mg(OH) 2 The same manufacturing method as in Example 1 was carried out, except that wet pulverization was carried out so that the final average particle diameter of the abrasive grains in Example 9 was 0.3 μm, to obtain an abrasive slurry in Example 9.

[0077] Comparative Example 1 In Comparative Example 1, the additive was magnesium hydroxide (Mg(OH) 2 , raw material particle size 3.5μm) to calcium hydroxide (Ca(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the raw material particle size was changed to 26.9 μm, to obtain an abrasive slurry according to Comparative Example 1.

[0078] Comparative Example 2 In Comparative Example 2, the additive was magnesium hydroxide (Mg(OH) 2 , raw material particle size 3.5μm) to produce aluminum hydroxide (Al(OH) 3 A manufacturing method similar to that of Example 1 was carried out, except that the raw material particle size was changed to 70.1 μm), to obtain an abrasive slurry according to Comparative Example 2.

[0079] Comparative Example 3 In Comparative Example 3, the same production method as in Example 1 was carried out except that no additive was added, to obtain an abrasive slurry according to Comparative Example 3.

[0080] Comparative Example 4 Comparative Example 4 is a cerium oxide abrasive (CeO 2 ), and magnesium hydroxide (Mg(OH) 2 A manufacturing method similar to that of Example 1 was carried out, except that the average particle diameter of the abrasive grains in the abrasive powder 2 was set to 0.7 μm, to obtain an abrasive slurry in Comparative Example 4.

[0081] Comparative Example 5 In Comparative Example 5, no additive was added, and cerium oxide (CeO 2 A manufacturing method similar to that of Example 1 was carried out, except that the average particle diameter of the abrasive grains in the abrasive powder 10) was set to 0.7 μm, to obtain an abrasive slurry in Comparative Example 5.

[0082] The following physical properties were measured for the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 5. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results are shown in FIG.

[0083] <Component analysis> Among the contents of the cerium oxide-based abrasive grains used in the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5, the total rare earth oxides (TREO) were measured by the oxalate precipitation-calcination-gravimetry method (unit: solid: mass%, liquid: g / L). As a pretreatment for the measurement, if the measurement object was a solid (abrasive raw material or abrasive), it was dissolved with nitric acid, perchloric acid, and hydrogen peroxide, and boiled. If the measurement object was a liquid, it was boiled as it was. Specifically, 100 ml of the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5 were placed in a glass beaker, and heated and dried at 120°C for 24 hours to make them into a dry powder state, and then dissolved by adding 5 mL of 60% nitric acid, 5 mL of 60% perchloric acid, and 1 mL of 35% hydrogen peroxide water, and then boiled to obtain the measurement samples according to Examples 1 to 9 and Comparative Examples 1 to 5. The total rare earth oxide (TREO) content of the measurement samples according to Examples 1 to 9 and Comparative Examples 1 to 5 was measured by the oxalate precipitation-calcination-gravimetry method. 2The / TREO was calculated by dissolving the measurement sample obtained by the above-mentioned total rare earth oxide (TREO) measurement by adding 5 mL of 60% nitric acid, 5 mL of 60% perchloric acid, and 1 mL of 35% hydrogen peroxide solution, and measuring it by the ICP-OES method. 2 O 3 / TREO,Pr 6 O 11 / TREO, Nd 2 O 3 The fluorine (F) content was calculated in the same manner for / TREO. The fluorine (F) content (mass%) in the measurement sample was calculated by dissolving the measurement sample in an alkali solution and extracting it with hot water, and measuring the F concentration in the solution using the fluoride ion electrode method.

[0084] The content of magnesium hydroxide-based abrasive grains used in the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 5 was determined by adding 5 mL of 60% nitric acid, 5 mL of 60% perchloric acid, and 1 mL of 35% hydrogen peroxide water to the above-mentioned solid (abrasive raw material or abrasive) measurement sample, decomposing by heating to form a solution, and measuring the Mg concentration using an ICP-OES device. The magnesium hydroxide content was calculated by estimating the content by multiplying this by the hydroxide coefficient. The hydroxide coefficient is 2.40 as described above.

[0085] <Particle size evaluation> The cerium oxide (CeO 2 ), magnesium hydroxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ), aluminum hydroxide (Al(OH) 3The average particle diameter of the abrasive grains is the particle diameter (D50) measured by particle diameter distribution measurement using dynamic light scattering. Here, the particle size distribution was evaluated using a zeta potential, particle diameter, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle diameter analysis-dynamic light scattering method", and the particle diameter (D50) at a volume-based cumulative fraction of 50% was measured. In addition, the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5 were diluted with pure water as necessary so that the solid content concentration in each abrasive slurry was 0.005% by mass to 0.1% by mass, and the measurement samples were prepared by filtering the measurement samples with a filter having a pore size of 11 μm immediately before the measurement, and ultrasonic treatment was performed for 3 minutes with an ultrasonic cleaner (manufactured by AS ONE Co., Ltd.: VS-100III). In addition, the liquid temperature of the measurement samples was adjusted to 25°C. The particle size (D50) refers to the median size (D50) which is the particle size showing the 50% integrated value of the integrated distribution curve.

[0086] <Polishing rate measurement test> The polishing rates of the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 5 were evaluated by the following procedure. The object to be polished was soda lime glass with a diameter of 60 mm. The polishing device used was a single-sided polishing machine manufactured by MAT Corporation. The polishing pad attached to the platen was a polyurethane polishing pad. Furthermore, the abrasive slurries used in the measurements were those of Examples 1 to 9 and Comparative Examples 1 to 5, in which the abrasive grain concentration was adjusted to 100 g / L. The supply rate of the abrasive slurry was set to 600 mL / min, and the pressure on the polishing surface was set to 9.8 kPa (100 g / cm). 2), and the rotation speed of the polishing machine was set to 60 rpm. Then, the polishing process was performed, and the mass of the soda-lime glass to be polished was measured before and after the polishing process to determine the amount of mass loss of the soda-lime glass due to the polishing process, and the polishing rate was calculated based on this value. The polishing rate after the polishing process was performed for 20 minutes was taken as the initial rate, and the polishing rate after the polishing process was performed for 6 hours was taken as the aging rate. If the initial rate was 0.45 μm / min or more, it was evaluated as "〇〇 (VERY GOOD)", if it was 0.40 μm / min or more and less than 0.45 μm / min, it was evaluated as "〇 (GOOD)", and if it was less than 0.40 μm / min, it was evaluated as "× (BAD)". If the aging rate was 80% or more of the initial rate, it was evaluated as "〇〇 (VERY GOOD)", if it was 60% or more and less than 80% of the initial rate, it was evaluated as "〇 (GOOD)", and if it was less than 60% of the initial rate, it was evaluated as "× (BAD)". The rate over time is preferably 0.2 μm / min or more, more preferably 0.32 μm / min or more, and particularly preferably 0.36 μm or more.

[0087] <Polishing accuracy evaluation> The polished surface of the soda lime glass that had been polished for 6 hours in the above-mentioned polishing rate measurement test was washed with pure water and dried in a dust-free state, after which the polishing accuracy was evaluated. The polishing accuracy was evaluated by measuring the polished surface after the polishing process in a measurement range of 10 μm × 10 μm using an atomic force microscope (AFM; Hitachi High-Tech Science AFM5400L) and calculating the surface roughness Ra of the polished surface. If the surface roughness Ra was less than 0.24 nm, it was evaluated as "〇〇 (VERY GOOD)", if it was 0.25 nm or more and less than 0.30, it was evaluated as "〇 (GOOD)", and if it was 0.30 nm or more, it was evaluated as "× (BAD)".

[0088] <pH measurement> The pH of the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5 was measured using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-53) after confirming that the liquid temperature was stable at 25° C. The pH measured after 20 minutes of polishing treatment was defined as the initial pH, and the pH measured after 6 hours of polishing treatment was defined as the time-dependent pH.

[0089] As shown in FIG. 1, the abrasive slurries of Examples 1 to 9 contained magnesium hydroxide-based abrasive grains as an additive, and thus deterioration over time was suppressed even when the average grain size of the cerium oxide-based abrasive grains and magnesium hydroxide-based abrasive grains was 0.01 μm to 0.5 μm.

[0090] The abrasive slurries of Examples 1 to 9 contained at least one dispersant selected from sodium citrate, sodium gluconate, and sodium tartrate, and thus deterioration over time was suppressed.

[0091] The polishing rate of the polishing slurries according to Examples 1 to 9 was suppressed from decreasing with time, and the surface roughness Ra was also excellent. On the other hand, the polishing slurries according to Comparative Examples 1 and 2 caused excessive aggregation with time during polishing, making polishing impossible or interrupting the polishing process. The polishing slurries according to Comparative Examples 4 and 5 had a surface roughness Ra of 0.30 nm or more because the average particle size of the cerium oxide abrasive grains or magnesium hydroxide abrasive grains was large.

[0092] In the abrasive slurries of Examples 1 to 9, the pH also showed little change over time.

[0093] In the abrasive slurries of Examples 1 to 9, when the abrasive slurry was taken as 100 mass%, the content of cerium oxide-based abrasive grains was 0.5 mass% or more and 40 mass% or less, and the content of magnesium hydroxide-based abrasive grains was 0.005 mass% or more and 20 mass% or less, and a good polishing rate was achieved.

[0094] The abrasive slurries according to Examples 1 to 9 had a weight ratio of magnesium hydroxide-based abrasive grains to cerium oxide-based abrasive grains of 1.25×10 -4 When the ratio was from 1 to 40, a decrease in the polishing rate could be suppressed.

[0095] In the abrasive slurries according to Examples 1 to 9, the cerium oxide-based abrasive grains have a Ce content of CeO 2 The La content is 100 mass% or less when converted to La. 2 O 3 The F content is 40 mass% or less in terms of F conversion, the F content is 10 mass% or less in terms of F conversion, and the Pr content is Pr 6 O 11 The Nd content is 10 mass% or less when converted to Nd 2 O 3 When the converted amount was 10 mass % or less, a good polishing rate could be achieved.

[0096] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]

[0097] The polishing rate of the polishing slurry according to the present invention is not easily decreased with time, and the pH fluctuation is suppressed, so that the polishing slurry according to the present invention is suitable as a polishing material used in the CMP method. In addition, since the polishing rate of the polishing slurry according to the present invention is not easily decreased with time, and the pH fluctuation is suppressed, the polishing slurry can be used for a longer period of time than before. Therefore, the amount of the product itself and the waste associated therewith can be reduced, and the energy costs during production and waste disposal can also be reduced. These points make it possible to achieve the sustainable management and efficient benefits of natural resources, as well as decarbonization (carbon neutrality).

Claims

1. Cerium oxide abrasive grains; Magnesium hydroxide abrasive grains; A dispersant; A solvent; It consists only of The abrasive slurry is characterized in that the average particle size of the cerium oxide-based abrasive grains and the magnesium hydroxide-based abrasive grains is 0.01 μm or more and 0.5 μm or less.

2. A cerium oxide abrasive, Magnesium hydroxide abrasive grains; A dispersant; an abrasive slurry having a solvent, The abrasive slurry does not contain a chelating agent, The abrasive slurry is characterized in that the average particle size of the cerium oxide-based abrasive grains and the magnesium hydroxide-based abrasive grains is 0.01 μm or more and 0.5 μm or less.

3. 3. The abrasive slurry according to claim 1, wherein the solvent contains water.

4. 3. The abrasive slurry according to claim 1, wherein the dispersant comprises at least one selected from the group consisting of organic acid alkali metal salts, phosphoric acids, and polymer dispersants.

5. 5. The abrasive slurry according to claim 4, wherein the organic acid alkali metal salt comprises at least one selected from the group consisting of sodium citrate, sodium gluconate, and sodium tartrate.

6. 3. The abrasive slurry according to claim 1, wherein the cerium oxide-based abrasive grains are cerium oxide abrasive grains.

7. When the abrasive slurry is 100 mass %, The content of the cerium oxide-based abrasive grains is 0.5% by mass or more and 40% by mass or less, 3. The abrasive slurry according to claim 1, wherein the content of the magnesium hydroxide-based abrasive grains is 0.005% by mass or more and 20% by mass or less.

8. The weight ratio of the magnesium hydroxide-based abrasive grains to the cerium oxide-based abrasive grains is 1.25×10 -4 3. The abrasive slurry according to claim 1, wherein the abrasive slurry has a molecular weight of 40 or more.

9. The cerium oxide-based abrasive grains, when the cerium oxide-based abrasive grains are taken as 100 mass %, Ce content is CeO 2 is 100% by mass or less in terms of mass conversion, The La content is La 2 O 3 is 40% by mass or less in terms of The F content is 10% by mass or less in terms of F, Pr content is Pr 6 O 11 is 10% by mass or less in terms of Nd content is Nd 2 O 3 This is calculated to be 10% by mass or less. The abrasive slurry according to claim 1 or 2.

10. 3. A polishing method comprising polishing an object to be polished with the abrasive slurry according to claim 1.

Citation Information

Patent Citations

  • Grinding slurry

    CN106916566A

  • Stable aqueous slurry suspension

    JP2011524814A

  • Slurry and polishing method of substrate using the same

    JP2017063190A

  • In-situ generation of aqueous, semi-aqueous, and non-aqueous slurry suspensions of viscous particles for separating and suspending inert and abrasive particles in a dispersing medium

    JP2019520989A

  • Polishing slurry and method of polishing substrate by using the polishing slurry

    US20190292406A1